Evaluation of the Effect of Tofacitinib Exposure on Outcomes in Kidney Transplant Patients. Issue 6 (3rd February 2015) - Vincenti, F.; Silva, H. T.; Busque, S.; O'Connell, P. J.; Russ, G.; Budde, K.; Yoshida, A.; Tortorici, M. A.; Lamba, M.; Lawendy, N.; Wang, W.; Chan, G.
<x xml:space="preserve">Abstract</x> Tofacitinib fixed‐dose regimens attained better kidney function and comparable efficacy to cyclosporine (CsA) in kidney transplant patients, albeit with increased risks of certain adverse events. This post‐hoc analysis evaluated whether a patient subgroup with an acceptable risk‐benefit profile could be identified. Tofacitinib exposure was a statistically significant predictor of serious infection rate. One‐hundred and eighty six kidney transplant patients were re‐categorized to above‐median (AME) or below‐median (BME) exposure groups. The 6‐month biopsy‐proven acute rejection rates in AME, BME and CsA groups were 7.8%, 15.7% and 17.7%, respectively. Measured glomerular filtration rate was higher in AME and BME groups versus CsA (61.2 and 67.9 vs. 53.9 mL/min) at Month 12. Fewer patients developed interstitial fibrosis and tubular atrophy (IF/TA) at Month 12 in AME (20.5%) and BME (27.8%) groups versus CsA (48.3%). Serious infections occurred more frequently in the AME group (53.0%) than in BME (28.4%) or CsA (25.5%) groups. Posttransplant lymphoproliferative disorder (PTLD) only occurred in the AME group. In kidney transplant patients, the BME group preserved the clinical advantage of comparable acute rejection rates, improved renal function and a lower incidence of IF/TA versus CsA, and with similar rates of serious infection and no PTLD.